IMPLEMENTASI EDUTAINMENT PADA MATA PELAJARAN PRODUKTIF FARMASI DI SMK MA’ARIF NU 2 AJIBARANG - Elsa Rakhmanita; Muhammad Hanif (STKIP Pesisir Selatan, 2026)
This qualitative research uses a case study approach to implement edutainment in productive subjects at SMK Ma'arif NU 2 Ajibarang. This study aims to describe the implementation of edutainment in the productive subject of Pharmacy, namely the Health Law (UUK). Learning implements edutainment through the use of a 3-dimensional bulletin board (wallpaper). Data collection was conducted using interviews, observation, and documentation. The data analysis technique used was the data analysis technique according to Miles and Huberman, which consists of data collection, data reduction, data presentation, and drawing conclusions. The results show that the implementation of edutainment in the productive subject of Pharmacy (UUK) was carried out over four meetings as outlined in the Lesson Implementation Plan (RPP). The learning process began with an introduction to the material, group formation, and the creation of the 3-dimensional bulletin board concept, concept presentation, and the wall board creation process. Edutainment can create more active learning, strengthen group collaboration, foster creativity, and create a more enjoyable learning experience. The implementation of edutainment in vocational high school education is expected to be applied to both productive and adaptive normative subjects.